Thematic Learning Innovation Approaching SCI (Smart, Creative, Innovative) Plus Elementary Schools in the Covid-19 Pandemic Era - Utami, Ratnasari Diah; Alfalah, Zona Abdul Azis; Prayitno, Harun Joko; Desstya, Anatri; Kartini, Nurul Hikmah; Negara, Santosa Pradana Putra Setya (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
The impact of the Covid-19 pandemic has affected the teaching and learning process for students. The learning process that was initially carried out face-to-face is now replaced by other methods. Various innovations were carried out by teachers to convey thematic dissemination of the Covid-19 pandemic. The purpose of this research is to describe thematic learning innovations in the era of the Covid-19 pandemic. This study uses a descriptive method with a qualitative approach. The informants consisted of the principal, homeroom teacher, and students. Data collection techniques by means of interviews, observations, and documentation. This study uses triangulation techniques and source triangulation in testing the validity of data. The data analysis technique uses Creswells theory. Based on the results of the research, it can be seen that thematic learning innovations in this pandemic era are carried out in various ways, namely: (1) Using the SCI (Smart, Creative, Innovative) Online Media application, whose innovation is in the form of creating various question types and High Order Thinking Skills (HOTS) levels, (2) Zoom Meet innovation is the delivery of various learning methods, conducting virtual group discussions, evaluation in the form of quizzes, (3) YouTube innovation in the form of a video with a background in the form of Microsoft PowerPoint, which contains material and uses comments on YouTube as attendance. (4) the use of Microsoft PowerPoint; the innovation is in the form of creating summary modules from thematic learning materials. Online learning using these innovations can effectively deliver thematic learning materials in distance learning.